DEVELOPMENT OF THE METHOD OF CRYPTOCOMPRESSION CODING OF IMAGES BASED ON A FLOATING NONDETERMINISTIC PROCESSING SCHEME - Barannik, Vladimir; Sidchenko, Serhii; Barannik, Dmitriy; Barannik , Valery; Shulgin, Sergii; Turenko, Serhii (Ukrainian Information Security Research Journal, 2022)
In the process of managing the objects of crisis infrastructure and during their protection, digital video images are used. Their volumes are constantly growing and requirements are imposed on them to maintain maximum quality while maintaining confidentiality. Therefore, a scientific and applied problem is relevant, which consists in increasing the confidentiality of video information in the conditions of ensuring its reliability and availability. To solve it, the one-stage method of cryptocompression coding of images in a differentiated basis based on the use of non-equilibrium positional coding technology was further improved. The difference between this method and the known ones is as follows. First, the floating coding scheme is organized within the entire image plane, when image elements belonging to different blocks of video data participate in the formation of the code values of the information component. For this, a scheme has been developed for linearizing coordinates from a four-dimensional representation of an element in a two-dimensional matrix, which determine the coordinates of a block in the image plane and coordinates of an element in this block, into a one-dimensional coordinate for one-to-one representation of this element in a vector. Secondly, two degrees of uncertainty are additionally used, which consist of the non-deterministic length of the code values of the cryptocompression codograms and the non-deterministic number of elements involved in their formation. This makes it possible to increase the cryptographic strength and availability of video data without loss of credibility.